Efektifitas Mediator Dalam Melaksanakan Mediasi Online Pada Perkara Gugatan Perceraian di Pengadilan Agama Bandung - Dewi, Ni Putu Juwanita (University of Merdeka Malang, 2024)
This research aims to analyze the effectiveness of the mediator's role in divorce cases using online mediation at the Bandung Religious Court, because data from various sources states that Bandung is one of the contributors to the highest divorce rate in West Java. Apart from analyzing the effectiveness of the mediator's role in divorce cases using online mediation, it also analyzes the supporting and inhibiting factors for the effectiveness of the mediator's role in the Bandung Religious Courts. The type of research is sociological juridical research using descriptive qualitative data analysis with research methods taking primary data with in-depth interviews with judge mediators, religious court clerks, in the city of Bandung as well as conducting observations and reviewing related documents, especially regarding the effectiveness of implementing online mediation in the religious courts. The research results found that the role of mediators in dealing with divorce cases using online mediation was not effective enough because there was a strong intention of the parties to remain divorced, the number of mediators was still limited compared to the number of divorce lawsuits registered, and there was a lack of socialization on the procedures for carrying out online mediation. The input regarding the effectiveness of mediators so that they can be effective and optimal in carrying out online mediation, especially for divorce cases at the Bandung Religious Court, namely the addition of mediators and the existence of periodic training or socialization for mediators to carry out online mediation procedures in accordance with PERMA Number 3 of 2022 concerning the Implementation of Online Mediation and the need for periodic socialization regarding the benefits and procedures of mediation, especially mediation online to the community and so that it can be followed up and applied in the religious court.